Qualitätsverbessernde Maßnahmen in der Versorgung von kritisch kranken Intensivpatienten mit Nierenersatztherapie bei akuter Nierenschädigung - Kindgen-Milles, Detlef; Heering, Peter; Meersch-Dini, Melanie; Schmitz, Michael; Oppert, Michael; John, Stefan; Joerres, Achim; Zarbock, Alexander; Willam, Carsten (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2020)
Renal replacement therapy is after mechanical ventilation one of the most important and frequently used organ replacement therapies in daily routine intensive care practice. In contrast to mechanical ventilation, quality standards for renal replacement therapy are less well known and defined. In this position paper of the German Interdisciplinary Association for Intensive Care and Emergency Medicine, we describe quality standards of renal replacement procedures in order to improve therapy of patients with severe acute kidney injury.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Acute renal failure; Dialysis; Hemofiltration; Quality standards; Renal replacement therapy